(untitled) (Revista de Física Médica, 2025)
In 2011, the CSN (Nuclear Safety Council), SEPR (Spanish Society for Radiological Protection), and SEFM (Spanish Society of Medical Physics) published a consensus document on release criteria for patients treated with I-131. However, despite the increasing use of metabolic therapies, no similar document exits for other radionuclides. Therefore, this study aims to establish restriction periods for [177Lu]Lu-DOTA-TATE and [177Lu]Lu-PSMA-617 treatments, applying the methodology of the above mentioned document while accounting for the number of cycles per treatment, as recommended by the CSN. As a result, four tables – categorized by radiopharmaceutical type and time of radiological discharge – were developed to facilitate the determination of restriction periods based on the release dose rate at 1 meter and the patient’s social and occupational situation. Compared to metastatic patients treated with I-131, it was found that although the clearance of Lu-177 is faster, considering the total number of treatment cycles results in longer overall restrictions. This finding underscores the need to review current release criteria of these patients to optimize the radiological protection of relatives and co-workers, who may be exposed to 4–6 radiation events within a 6–8-month period.